Fallacious Administrative and Judicial Approach to Farmers’ Loan - Mishra, Rabindra Kumar (Journal of Commerce and Trade, 2011)
This paper analyses the responsibility of judiciary and financial institutions to save the farmers from debt trap and suicide. Really the farmers are not improving by the application of high yielding seeds, quality fertilizers, and powerful pesticides rather they are victimised for this being over shadowed by loan. It is rightly felt the need of a debate and solution to the problem of loan, subsidy, repayment of loan, honesty of related administration, untimely change of weather leading to crop failure, lack of required help lack of arrangement of suitable rate and market. So, in this paper different dimension of judicial provision, constitutional arrangement, responsibility of financial institution and government policies etc have been examined to safeguard the interest of farmers for over all agricultural development of the nation.